Managerial Subordinacy: A Neglected Aspect of Organizational Hierarchies - Laurent, André (Academy of Management Review, 1978)
Following preliminary inquiry into the nature and effects of organizational hierarchies, the one-sided superordinate view of the managerial role is illustrated and explored through a review of the organization and management field. An argument is proposed to integrate managerial subordinacy into the picture and to enlarge organizational thinking through cross-cultural research.